Students’ Perceptions Toward the Process of Online English Language Teaching and Learning - yufhita, Syarifah Ismia; Sutapa Yuliana, Yohanes Gatot; Apriliaswati, Wardah Rahayu; Rahmani, Eka Fajar (Lingual Journal of Language and Culture; Vol 15 No 1 (2023): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2023.v15.i01.p07, 2023)
The adoption of online learning is one indication of increased technological empowerment in education. Teachers apply online learning to achieve learning goals even at a distance. However, the implementation of online learning falls short of educators' expectations. This study aimed to discover the perceptions of eleventh-grade students at SMA Taman Mulia and the challenges they confront during online English language teaching and learning. This study used an online survey to collect the data. From the data, 61% of students negatively perceived online English learning whereas 57% of students agreed that materials become harder to understand during online English language teaching and learning. Meanwhile, students gave positive perceptions regarding assignments and the teacher's explanations. The study also found that most students faced challenges such as incomprehension, lack of vocabulary and fluency, lack of communication, unmotivated, limited time, and low signal and internet quota. Therefore, it is clear that online English language teaching and learning require more focus in terms of both materials’ delivery and students’ challenges, particularly those related to understanding.